HISTOMORPHOMETRY OF THE DEXTER VENTRICLE OF LOCAL BALI DUCKS AT GROWTH PHASE - Pasaribu, Delima Marsinta Ida; Setiasih, Ni Luh Eka; Heryani, Luh Gde Sri Surya; Berata, I Ketut; Susari, Ni Nyoman Werdi; Suatha, I Ketut (Buletin Veteriner Udayana, 2024)
Heart is the main organ in blood circulation which plays a role in pumping blood to all body cells and returning to the heart. Avian heart has four chambers consisting of two atria (dexter and sinister) and two ventricles (dexter and sinister), each chamber has three layers of walls consisting of epicardium, myocardium and endocardium. This study aimed to obtain information about the histological structure and histomorphometry of ventriculus dexter of the bali duck’s heart at grower phase. The study sample used 18 bali ducks, which were divided into two gender groups and each consisted of 9 ducks (3 months old). Ventriculus dexter sample was the processed into a histology preparation by Haematoxylin-Eosin (HE) staining. Anatomy and histology results were analyzed using descriptive qualitative analysis, while histomorphometry used the anova test with mean estimation using the SPSS 26 program. The mean thickness of the epicardium, myocardium, and endocardium in males respectively were 43,11 ± 12,05µm, 1.145,19 ± 133,99µm, 23,41 ± 6,91µm. While in females respectively were 34,98 ± 17,03µm, 1.367,41 ± 412,43µm, 11,86 ± 5,06µm. Histomorphometric data that has been analyzed shows that the results of measuring the thickness of the endocardium are significantly different (P<0,05), while measuring the thickness of the epicardium and myocardium was not significantly different (P>0,05).. It can be concluded that the anatomical structure of the heart and the histological structure of the ventriculus dexter of bali ducks didn’t differ between treatment males and females, but there were differences in the histomorphometry of the endocardial layer. Research on the heart of balinese ducks is still rarely carried out, so further research is needed on the structure and histomorphometry of the epicardium layer, myocardium layer, and endocardium layer of the dexter ventricle or other heart chambers in bali ducks at different phases.